2013
DOI: 10.1021/ja408073m
|View full text |Cite
|
Sign up to set email alerts
|

Dichotomous Hydrogen Atom Transfer vs Proton-Coupled Electron Transfer During Activation of X–H Bonds (X = C, N, O) by Nonheme Iron–Oxo Complexes of Variable Basicity

Abstract: We describe herein the hydrogen-atom transfer (HAT)/ proton-coupled electron-transfer (PCET) reactivity for FeIV-oxo and FeIII-oxo complexes (1–4) that activate C-H, N-H, and O-H bonds in 9,10 dihydroanthracene (S1), dimethylformamide (S2), 1,2 diphenylhydrazine (S3), p-methoxyphenol (S4), and 1,4-cyclohexadiene (S5). In 1–3, the iron is pentacoordinated by tris[N'-tert-butylureaylato)-N-ethylene]aminato ([H3buea]3−) or its derivatives. These complexes are basic, in the order 3 >> 1 > 2. Oxidant 4, [FeIVN4Py(O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
256
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(277 citation statements)
references
References 128 publications
18
256
1
2
Order By: Relevance
“…In a theoretical work, Usharani et al [179] linked the basicity of the Fe IV =O oxidant with a mechanism for HAA, i.e., the concerted H-atom transfer (HAT) versus the proton-coupled electron transfer (PCET). Using valence bond based arguments, they concluded that a less basic oxidant exhibits a higher oxyl character on the oxo group that is required for the more concerted HAT (more homolytic)…”
Section: Reduction Potential / Basicity Correlated To H-atom Abstractmentioning
confidence: 99%
“…In a theoretical work, Usharani et al [179] linked the basicity of the Fe IV =O oxidant with a mechanism for HAA, i.e., the concerted H-atom transfer (HAT) versus the proton-coupled electron transfer (PCET). Using valence bond based arguments, they concluded that a less basic oxidant exhibits a higher oxyl character on the oxo group that is required for the more concerted HAT (more homolytic)…”
Section: Reduction Potential / Basicity Correlated To H-atom Abstractmentioning
confidence: 99%
“…We conjectured that the observed small reaction barrier could be well explained in terms of the hydrogen atom transfer (HAT) mechanism [18]. However, we later learned from Usharani et al's computational analysis of the H-abstraction reactions of synthetic nonheme iron-oxo complexes that spin natural orbital (SNO) analysis provides a useful orbital signature of PCET in the reactions of iron-oxo complexes [19]. Thus, when PCET takes place, the SNO is not localized onto the reacting X H bond (X C, N, ...), but rather is a or mixed -lone-pair orbital that does not point to the oxo unit [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…However, we later learned from Usharani et al's computational analysis of the H-abstraction reactions of synthetic nonheme iron-oxo complexes that spin natural orbital (SNO) analysis provides a useful orbital signature of PCET in the reactions of iron-oxo complexes [19]. Thus, when PCET takes place, the SNO is not localized onto the reacting X H bond (X C, N, ...), but rather is a or mixed -lone-pair orbital that does not point to the oxo unit [19,20]. We felt that using the SNO approach and other theoretical techniques, the H-abstraction from UDMH by P450 Cpd I should be further studied in greater depth.…”
Section: Introductionmentioning
confidence: 99%
“…Reactions in which electron and proton travel together as a true hydrogen atom will be called hydrogen atom transfer (HAT); the more general term cPCET will be used only when proton and electron are transferred in concert, but do not travel together, a definition similar to the one used by Shaik and co‐workers 7a. Scheme 1 shows two representative cases, which we will discuss in detail below.…”
mentioning
confidence: 99%